Souter liedekens gemaeckt ter eeren Gods, op alle die Psalmen van David tot stichtinge, ende een gheestelijcke vermakinge van alle christen menschen - Zuylen van Nijevelt, Willem van ?-1543 (Utrecht de Roy, 1598)
The Souterliedekens (literal: Psalter-songs) is a Dutch metrical psalter, originally published in 1540 in Antwerp. The collection remained very popular throughout the century. The metrical rhyming psalms were probably arranged by Willem van Zuylen van Nijevelt (d. 1543), a nobleman from Utrecht, who created the melodies out of folk songs from the Low Countries (though some melodies have a German or French origin). This publication has great value, because the original publisher (Symon Cock) not only added the phrase 'sung to the tune of...', but also provided the actual music (melody) with the texts. Nowadays many of the folk song melodies that were known at that time can only be reconstructed because they have survived in the "Souterliedekens".
Originally published in 1540
Ex libris Seth Gaaikema (1939-2014), a Dutch cabaret artist, musical writer and translator.
Keywords: 16th Century (1501-1600); Song; Poetry; Folk music; Psalm; Religion; Contrafactum; Netherlands